Pengaruh Pemberian Tehnik Sitz Bath Terhadap Tingkat Nyeri Luka Perineum Pada Ibu Nifas - Qiftiyah, Mariyatul; Cholila, Nur (Sekolah Tinggi Ilmu Kesehatan Adila Bandar Lampung, 2025)
Background: Postpartum mothers with perineal wounds require appropriate care to prevent health complications, pain and discomfort. The aim of this study was to determine the effect of giving the sitz bath technique on the level of perineal wound pain in postpartum mothers on day 3 at TPMB Antis'in. Methods:Quasy Experiment research design, the independent variable is sitz bath technique depending on the level of perineal wound pain. The population of mothers and toddlers at TPMB Antis'in is 18 people and the sample is 16 respondents. Simple random sampling technique, data collection instrument for the level of perineal wound pain before and after treatment was measured using the NRS (Numeric Rating Scale) questionnaire and the Wilcoxon statistical test with α